Dysfunction of the Sacroiliac Joints - Pinto Camelo, António; Serviço de Fisiatria, Centro Hospitalar do Porto, Porto, Portugal (2019)
The sacroiliac joints (SI) dysfunction is a condition when the normal joint biomechanics is affected, thereby leading to a restricted or excessive motion. Although it is a relatively common pathology, it is often underdiagnosed. This study aims to characterize this entity, particularly regarding the anatomy, biomechanics and physiopathology, as well as to describe the most relevant clinical features and treatment. For this purpose, we performed a narrative review of the literature published until May 2016 in medical databases. SI is the strongest and most stable diarthroses that support body weight. The torsional forces exerted on the SI are significant and are controlled by ligaments around them, particularly the sacrospinous and sacrotuberous ligaments. Both the ischiotibial and abdominal muscles appear to have a considerable lever effect, forcing the iliac to a posterior rotation. Clinical history and objective evaluation (eg, trunk flexion pattern and specific maneuvers) are fundamental for diagnosis and to exclude other potential differential diagnoses, such as discopathy and lumbar facet dysfunction. Treatment involves a multimodal approach that should include patient education, pharmacological treatment, physical agents, manual, muscle energy and stabilization techniques, and prolotherapy.